The urban–rural gap in healthcare infrastructure: does government ideology matter? - Niklas Potrafke; Felix Roesel (Regional Studies, 2020)
Spatial inequalities in publicly provided goods such as healthcare facilities have substantial socioeconomic effects. Little is known, however, about why publicly provided goods diverge among urban and rural regions. This study exploits narrow parliamentary majorities in German states between 1950 and 2014 in a regression discontinuity (RD) framework to show that government ideology influences the urban–rural gap in public infrastructure. Left-wing governments relocate hospital beds from rural regions. It is proposed that left-wing governments do so to gratify their more urban constituencies. In turn, spatial inequalities in hospital infrastructure increase, which seems to influence general and infant mortality.
Keywords: D72; H42; I18; 330; publicly provided goods; spatial inequalities; political business cycles; government ideology; healthcare; hospitals